2019
DOI: 10.3389/fmicb.2019.01226
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Digital PCR for Estimating Absolute Abundances of Widespread Pelagibacter Viruses

Abstract: Absolute abundances of prokaryotes are typically determined by FISH. Due to the lack of a universal conserved gene among all viruses, metagenomic fragment recruitment is commonly used to estimate the relative viral abundance. However, the paucity of absolute virus abundance data hinders our ability to fully understand how viruses drive global microbial populations. The cosmopolitan marine Pelagibacter ubique is host for the highly widespread HTVC010P pelagiphage isolate and the extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
(107 reference statements)
0
24
0
Order By: Relevance
“…A follow-up study showed that 37-F6 virus and relatives were present in sorted single Pelagibacter cells (Martinez-Hernandez et al, 2019), while recent transcriptomic data provided first evidence of high in situ activity in coastal temperate waters of the NE Atlantic (Alonso-Sáez et al, 2018). Recently, droplet digital PCR (dPCR) estimated that the absolute abundances of free viral particles of virus 37-F6 in the Mediterranean Sea and the Gulf of Maine ranged between hundreds to thousands (360-8,510) viruses mL-1 seawater; within the abundance range of the pelagiphage isolate HTVC010P (Martinez-Hernandez, et al, 2019b). dPCR data also showed that the number of infecting 37-F6 viruses in coastal bacterioplankton (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study showed that 37-F6 virus and relatives were present in sorted single Pelagibacter cells (Martinez-Hernandez et al, 2019), while recent transcriptomic data provided first evidence of high in situ activity in coastal temperate waters of the NE Atlantic (Alonso-Sáez et al, 2018). Recently, droplet digital PCR (dPCR) estimated that the absolute abundances of free viral particles of virus 37-F6 in the Mediterranean Sea and the Gulf of Maine ranged between hundreds to thousands (360-8,510) viruses mL-1 seawater; within the abundance range of the pelagiphage isolate HTVC010P (Martinez-Hernandez, et al, 2019b). dPCR data also showed that the number of infecting 37-F6 viruses in coastal bacterioplankton (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For the TaqMan chip‐based dPCR assays, a previous validated probe and primer set named ddSeq4 (size of PCR amplicon band ≈100; Supporting Information Fig. S3A) was employed (Martinez‐Hernandez, et al ., ). First, we ensured by real‐time PCR that primer sets Seq6 and ddSeq4 used for TaqMan and SYBR chemistry assays had similar efficiencies and reproducibility for monitoring abundances of virus 37‐F6 genome (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 97%
“…dPCR comparison of SYBR Green I chip‐based dPCR chemistry versus TaqMan chip‐based dPCR with an environmental DNA template (bacterioplankton cell fraction) collected at Cape Huertas (Mediterranean Sea). Total number of infecting viruses per mL of seawater is indicated according to dPCR data correction by (Martinez‐Hernandez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…(Hewa et al, 2009;Jung et al, 2015a) antibody production resulting in false negative results using immunoassays, which can be up as long as 35-45 days for first generation HIV testing (Cornett and Kirn, 2013). Currently, dPCR is gaining popularity due to its ability to detect either DNA or RNA, with absolute gene quantification being more immune to background noise than conventional qPCR (Martinez-Hernandez et al, 2019). NA-based detection methods have revolutionized virus-related diagnostics (Roy et al, 2017) having the false negative window period HIV between 10 and 15 days (Branson and Stekler, 2011).…”
Section: Conventional Techniques For Detection Of Viral Diseasesmentioning
confidence: 99%